The giver - Lowry, Lois. (New York : harper collins, 1994)
Given his lifetime assignment at the Ceremony of Twelve, Jonas becomes the receiver of memories shared by only one other in his community and discovers the terrible truth about the society in which he lives.
"Laurel-leaf books."
Newbery Medal 1994
Keywords: Newbery Medal -- 1994; Fantasy -- Juvenile fiction; Control (Psychology) -- Juvenile Fiction; Social control -- Juvenile Fiction; Ethics -- Juvenile Fiction; Fantasy fiction